The Influence of Alginate and CaCl2 concentration Towards Betacyanin content and Antioxidant Activity of Red Dragon Fruit (Hylocereus Polyrhizus) restructuring product - Wira Wanti Bangalino; Lydia Ninan Lestario; Cucun Alep Riyanto (Journal of Natural Sciences and Mathematics Research, 2016)
The purpose of this study was to determine the effect of alginate and CaCl2 concentration of antioxidant activity and betacyanin content of restructuring product of red dragon fruit, and to determine the best formulation of the product restructuring that produces antioxidant activity and the content of the highest betacyanin on product restructuring. Data were analyzed by 4x2 Factorial Design and Randomized Completely Block Design (RCBD) with 4 replications. As the first factor is the alginate concentration which are 2 %, 3 %, 4 % and 5 %. The second factors are calcium cloride (CaCl2 ) 0.5 % and 0.75 %, while as the block is the time analysis. To test the differences between treatments means, the Honestly Significant of Differences (HSD) were used at 5% level of significant.The results showed that the higher concentrations of alginate and CaCl2 causes declining content of antioxidant activity and betacyanin, the best results are obtained is at a concentration of 2% alginate and CaCl2 0.5% with betacyanin levels 0.537 ± 0.062 mg/g dry weight basis and 0.132 ± 0.011 mg / g wet weight basis. The antioxidant activity of H. polyrhyzus restructuring amounted to 77.452% ± 0.624. ©2016 JNSMR UIN Walisongo. All rights reserved.